2008
DOI: 10.1002/elps.200700365
|View full text |Cite
|
Sign up to set email alerts
|

Separation of very hydrophobic analytes by MEKC. II. Carbon number equivalents as analyte descriptors – influence of the composition of the separation electrolyte

Abstract: The use of the parameter carbon number equivalent, N(c)(*), as analyte descriptor for neutral hydrophobic solutes in EKC is investigated. The carbon number equivalent of an analyte is defined analogously to the retention index, RI, however, it is directly calculated from the regression line plotting for the members of a homologous series the logarithm of the retention factor against the number of methylene units N(c) in the alkyl chain. This plot can be obtained by using simultaneously an iteration procedure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Taking alkyl phenones as reference solutes, N Ã C for a number of sassafras oil constituents were calculated for different compositions of the separation electrolyte (see Section 3) [29]. The resulting mean values and RSDs are given in Table 1.…”
Section: Carbon Numbers and Carbon Number Equivalentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Taking alkyl phenones as reference solutes, N Ã C for a number of sassafras oil constituents were calculated for different compositions of the separation electrolyte (see Section 3) [29]. The resulting mean values and RSDs are given in Table 1.…”
Section: Carbon Numbers and Carbon Number Equivalentsmentioning
confidence: 99%
“…However, in order to simplify further calculations we did not transfer retention data into retention indices but used carbon number equivalents N Ã C . In a previous publication [29], it was shown that for the analytes selected taking the homologous series of alkyl phenones as reference N Ã C is quasi-independent of the composition of the separation electrolyte regarding type and concentration of the modifier. Other publications [36,37] showed the independence of retention indices from the concentration of the PSP and the temperature.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The slope b of the regression plot shows the methylene selectivities that represent an average for the entire homologous series 106, 91. Huhn et al 111, 112, 119 proposed to use regression parameters together with determined values of t 0 and t ps as a set of parameters to characterize the properties of the pseudostationary phase. Consequently, the influence of additives on the properties of the BGE solution can be characterized using these four parameters.…”
Section: Use Of Homologous Series Of Analytesmentioning
confidence: 99%